Over-the-counter emergency contraception in Italy: ethical reflections and medico-legal issues - Scendoni, Roberto; Cingolani, Mariano; Cembriani, Fabio; Fedeli, Piergiorgio; Tambone, Vittoradolfo; Terranova, Corrado; De Micco, Francesco (Frontiers in Global Women's Health, 2023)
Although more than ten years have passed since the marketing of Ulipristal acetate in Europe, emergency contraception remains a complex issue with many scientific, legal, ethical and social implications. The topic is an example of the differences that can exist between scientific evidence, the certainties on which law is based, and social implications. This paper shows the incompleteness of the scientific reconstruction on the effects of emergency hormonal contraceptives and the dangerousness of the decision to alienate the supply of over-the-counter drugs from the general rules of health care. This report shows the incompleteness of the scientific reconstruction on the effects of emergency hormonal contraceptives and the dangerousness of the decision to alienate the supply of over-the-counter drugs from the general rules of health care. Various ethical and medico-legal issues will be addressed, also focusing attention on underage women whose sexual and reproductive health requires not abandoning them, but actually taking charge of them without medicalizing their choices.